EFFECT OF RECEIVABLE TURNOVER, SALES GROWTH, LEVERAGE AND COMPANY SIZE ON COMPANY PROFITABILITY (STUDY AT PT POS INDONESIA (PERSERO) REGIONAL REGION 6 MAKASSAR) - Made Nikko Mahayana; Ni Kadek Sinarwati; Putu Indah Rahmawati (Jurnal Ekonomi, 2023)
This study intends to examine the impact of leverage, sales growth, accounts receivable turnover, and firm size on profitability. Purposive sampling was the method of choice for sampling, and 34 offices were obtained which only used branch offices in Regional 6 Makassar. Multiple linear regression analysis is the technique utilized for data analysis. The findings indicated that in part receivables turnover has a positive effect on profitability at branch offices in regional 6 Makassar, partially sales growth has a positive effect on profitability at branch offices in regional 6 Makassar, partially leverage has a negative effect on profitability at branch offices in regional 6 Makassar, partially company size has a positive effect on the profitability variable at branch offices in regional 6 Makassar, simultaneously there is a significant influence between accounts receivable turnover, sales growth, leverage and company size on profitability. Receivable turnover and leverage are the factors that most influence the company's profitability so that more effort is needed in the receivables handling policies set by the company.